The Fundamental Constitutions for the Province of East New Jersey in America (1683) - (:unkn) unknown (My University, 1683)
Art. VII: Provided the state with the authority to arm and defend its forts,, castles, cities, and other places of defense. Also regulated the possession of firearms by citizens
Keywords: ARMED FORCES; POSSESSION